Narrative of the life of Frederick Douglass - Frederick Douglass (Boston, 1995)
Frederick Douglass is one of the most celebrated writers in the African American literary tradition, and his first autobiography is the one of the most widely read North American slave narratives. Narrative of the Life of Frederick Douglass, An American Slave was published in 1845, less than seven years after Douglass escaped from slavery. The book was an instant success, selling 4,500 copies in the first four months. Throughout his life, Douglass continued to revise and expand his autobiography, publishing a second version in 1855 as My Bondage and My Freedom. The third version of Douglass' autobiography was published in 1881 as Life and Times of Frederick Douglass, and an expanded version of Life and Times was published in 1892. These various retellings of Douglass' story all begin with his birth and childhood, but each new version emphasizes the mutual influence and close correlation of Douglass' life with key events in American history.
Includes appendix
Keywords: Biography